1992
DOI: 10.1007/bf01703083
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sequence analysis and expression of bovine PrP gene in mouse L-929 cells

Abstract: A cDNA clone encoding bovine scrapie-associated fibril protein, PrP, from a bovine brain cDNA library and six amplified genomic DNA clones of bovine PrP were characterized. These clones possessed specific characteristics observed in other animal PrP genes. However, the bovine PrP was divided into two types by the number of repeats. One possessed four octapeptide repetitive sequences, like other animal PrP genes, and consisted of 256 amino acids; the other had five such repetitive sequences and 264 amino acids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…1, bold line); Figure 2A shows the nucleotide sequence of 3407-bp of the bovine PrP non-coding region. Compared with the nucleotide sequence of the cDNA reported by Yoshimoto et al [40], we found that the 151-bp 5' non-coding region of the cDNA consisted of two exons separated by a 2445-bp intron ( Fig. 2A).…”
Section: Dna Sequencing and Mapping Of The 5'non-coding Region Of Thesupporting
confidence: 48%
See 2 more Smart Citations
“…1, bold line); Figure 2A shows the nucleotide sequence of 3407-bp of the bovine PrP non-coding region. Compared with the nucleotide sequence of the cDNA reported by Yoshimoto et al [40], we found that the 151-bp 5' non-coding region of the cDNA consisted of two exons separated by a 2445-bp intron ( Fig. 2A).…”
Section: Dna Sequencing and Mapping Of The 5'non-coding Region Of Thesupporting
confidence: 48%
“…The nucleotide sequence of the 5' end of the cDNA that was amplified and cloned into the plasmid was exactly identical to the 5' terminus of the cDNA reported by Yoshimoto et al [40] (Fig. 2A, bent arrow, +1).…”
Section: Dna Sequencing and Mapping Of The 5'non-coding Region Of Thementioning
confidence: 62%
See 1 more Smart Citation
“…These possibilities are compatible with the apparent ubiquity of exon 2 splicing in other mammals; exon 2-containing cDNAs have now been described in cattle (Yoshimoto et al 1992) and recent reanalysis of the Syrian hamster (SHa) PrP gene, for which exon 1 originally appeared directly spliced to exon 3 (Basler et al 1986). The reanalysis showed that whereas 90% of SHaPrP mRNAs in the brain exhibit exon 1-3 splicing, 10% include exon 2 sequences closely related to those of sheep and mouse (Li and Bolton 1997).…”
Section: Discussionmentioning
confidence: 52%
“…AB001468) contains the mariner element as well, although the original bovine cDNA entries in GenBank (accession nos. D10612 and D90545) (Yoshimoto et al 1992) were partial and did not extend to the mariner integration site.…”
Section: Human Prpmentioning
confidence: 99%